REDUCTION OF REAL POWER LOSS BY IMPROVED SHUFFLED FROG-LEAPING ALGORITHM - Kanagasabai, Lenin (International Journal of Research -GRANTHAALAYAH, 2018)
This paper presents Improved Shuffled Frog-Leaping (ISFL) algorithm for solving optimal reactive power problem. A new search-acceleration parameter has been introduced into the formulation of the original shuffled frog leaping (SFL) algorithm to create an adapted form of the shuffled frog algorithm for solving the reactive power problem. The shuffled frog-leaping algorithm draws its formulation from two other search techniques: the local search of the ‘particle swarm optimization’ technique; and the competitiveness mixing of information of the ‘shuffled complex evolution’ technique. Proposed Improved Shuffled Frog-Leaping (ISFL) algorithm has been tested in standard IEEE 30,57,118 & Practical 191 Utility (Indian) System bus test systems and simulation results show clearly about the better performance of the proposed algorithm in reducing the real power loss & control variables within the limits